Indicators of adversity recorded in hospitalisation records of children aged less than 5 years or their mothers: a record linkage study of children born in England in 2011 - Mukhtar, Toqir; Wijlaars, Linda; McGrath-Lone, Louise; Gilbert, Ruth (International Journal of Population Data Science, 2018)
Background Early identification of child adversity (comprising abuse, neglect, social or material adversity) is essential to target early interventions to safeguard children, and support vulnerable families. We determined the prevalence of indicators of adversity recorded in diagnostic codes in child and/or maternal hospital admissions in England. Data Source All birth admissions recorded in the NHS in England in 2011, and subsequent admissions up to 5 years old, linked to maternal records from 1 year before to up to 5 years after delivery. Methods Prevalence of adversity indicators in child and/or maternal admission records that reflect adversity-related injury (ARI), or social or material adversity (SMA). Results Among 646,956 live born children, 2.6% (95% CI: 2.6 to 2.7) had at least one adversity indicator by <5 years (0.8% ARI, 2.6% SMA). Cumulative prevalence was 1.1% in children aged <6 months, 1.2% in children aged <1 year, 2.1% by <=2 years, and 2.6% up to 5 years old. Combined prevalence in maternal and/or child records will be presented. Conclusion To inform health policy, clinical and prognostic significance of adversity indicators requires evaluation through linkage to health and welfare outcomes.